Driving anxiety and young older adults : the impact on health and well-being : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Hempel, Megan (Massey University, 2015)
The purpose of the current study was to examine the impact of driving anxiety on young older adults’ health and well-being, and determine if driving anxiety had a detrimental effect on health and well-being over and above the effect of socio-demographic factors. Research into this topic was needed because the effects of driving anxiety on functioning has not been widely researched, and the literature is sparse and limited to specific samples of the population. A small amount of research in New Zealand has shown that young older adults’ functioning may be affected by driving anxiety, but what is unknown is whether health and well-being are affected. Therefore, the current study used data from the Health, Work and Retirement Study (2008) to determine the impact of driving anxiety on 2,473 young older adults aged 55-72 years in New Zealand, and to identify if there was a relationship between driving anxiety and health and well-being. Hierarchical multiple regression analyses were used to analyse the relationships between driving anxiety and mental health, physical health and quality of life, while controlling for socio-demographic variables. The results demonstrated that driving anxiety was associated with poorer scores on the three aspects of health and well-being, and this effect was still present when socio-demographic variables were controlled for. In order to preserve good health and well-being for older adults, further research on the relationship between driving anxiety and health and well-being is needed to better understand the experience of driving anxiety, develop healthy and effective ways to promote continued driving, and maintain driving ability where possible and appropriate.
Keywords: Driving anxiety; Older people and driving; Older people's well-being